The strategic analysis of judicial behavior a comparative perspective - Epstein, Lee 1958-; Weinshall, Keren 1978- (Cambridge University Press, 2021)
The past decade has witnessed a worldwide explosion of work aimed at illuminating judicial-behavior: the choices judges make and the consequences of their choices. We focus on strategic accounts of judicial-behavior. As in other approaches to judging, preferences and institutions play a central role but strategic accounts are unique in one important respect: They draw attention to the interdependent - i.e., the strategic - nature of judicial decisions. On strategic accounts, judges do not make decisions in a vacuum, but rather attend to the preferences and likely actions of other actors, including their colleagues, superiors, politicians, and the public. We survey the major methodological approaches for conducting strategic analysis and consider how scholars have used them to provide insight into the effect of internal and external actors on the judges' choices. As far as these studies have traveled in illuminating judicial-behavior, many opportunities for forward movement remain. We flag four in the conclusion
Title from publisher's bibliographic system (viewed on 31 May 2021)
Keywords: Judicial process / Statistical methods